Is it possible to diagnose benign positional paroxysmal vertigo from primary care referrals to ENT clinic?. (2nd October 2017) - Yuen, Jason; Rashid, Mamun; Webber, Caitlin; Prior, Matthew
Abstract: Background: Ear, nose and throat (ENT) departments commonly receive referrals of dizzy patients from primary care. It is important to distinguish complex cases of dizziness without straightforward diagnoses from simple benign positional paroxysmal vertigo (BPPV) when triaging patients such that appropriate resources are diverted to the patients who need them. Objective: To assess efficiency in identifying BPPV among dizzy patients from GP referral letters. Methods: Four doctors with different ENT experience and one senior nurse participated to identify BPPV cases from primary care referral letters before the patients' clinic appointments. The diagnoses subsequently made in clinic were used to compare against the predictions made. Results: Forty-nine patients were included, of which 22% were diagnosed BPPV in clinic. The overall predictions were poor among the participants. The positive predictive values (PPV) varied between 0.23 and 0.35. Negative predictive values (NPV) varied between 0.78 and 0.86. The commonly described clinical features of BPPV also had low PPV of less than 0.3. Conclusions: The accuracy to identify BPPV from referral letters alone is poor among doctors of different experience. We believe this is due to insufficient details in the current letters. The introduction of referral proformas would likely aid diagnosis.